In-Depth Analysis of Human Neonatal and Adult IgM Antibody Repertoires - Hong, Binbin; Wu, Yanling; Li, Wei; Wang, Xun; Wen, Yumei; Jiang, Shibo; Dimitrov, Dimiter S.; Ying, Tianlei (Frontiers in Immunology, 2018)
Although high-throughput sequencing and associated bioinformatics technologies have enabled the in-depth, sequence-based characterization of human immune repertoires, only a few studies on a relatively small number of sequences explored the characteristics of antibody repertoires in neonates, with contradictory conclusions. To gain a more comprehensive understanding of the human IgM antibody repertoire, we performed Illumina sequencing and IMGT/HighV-QUEST analysis of IgM heavy chain repertoire of the B lymphocytes from the cord blood of neonates (CB), as well as the repertoire from peripheral blood of healthy adults (HH). The comparative study revealed unexpectedly high levels of similarity between the neonatal and adult repertoires. In both repertoires, the VDJ gene usage showed no significant difference, and the most frequently used VDJ gene was IGHV4-59, IGHD3-10, and IGHJ3. The average amino acid (aa) length of CDR1 (CB: 8.5, HH: 8.4) and CDR2 (CB: 7.6, HH: 7.5), as well as the aa composition and the average hydrophobicity of the CDR3 demonstrated no significant difference between the two repertories. However, the average aa length of CDR3 was longer in the HH repertoire than the CB repertoire (CB: 14.5, HH: 15.5). Besides, the frequencies of aa mutations in CDR1 (CB: 19.33%, HH: 25.84%) and CDR2 (CB: 9.26%, HH: 17.82%) were higher in the HH repertoire compared to the CB repertoire. Interestingly, the most prominent difference between the two repertoires was the occurrence of N2 addition (CB: 64.87%, HH: 85.69%), a process that occurs during V-D-J recombination for introducing random nucleotide additions between D and J gene segments. The antibody repertoire of healthy adults was more diverse than that of neonates largely due to the higher occurrence of N2 addition. These findings may lead to a better understanding of antibody development and evolution pathways, and may have potential practical value for facilitating the generation of more effective antibody therapeutics and vaccines.